2022
DOI: 10.1002/ecy.3629
|View full text |Cite
|
Sign up to set email alerts
|

Climatic stability, not average habitat temperature, determines thermal tolerance of subterranean beetles

Abstract: The climatic variability hypothesis predicts the evolution of species with wide thermal tolerance ranges in environments with variable temperatures, and the evolution of thermal specialists in thermally stable environments. In caves, the extent of spatial and temporal thermal variability experienced by taxa decreases with their degree of specialization to deep subterranean habitats. We use phylogenetic generalized least squares to model the relationship among thermal tolerance (upper lethal limits), subterrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…To date, conservation of subterranean ecosystems has been dominated by problem‐based studies focused on identifying the main drivers associated with subterranean biodiversity decline (Mammola et al ., 2019a; Gerovasileiou & Bianchi, 2021). For example, we have elucidated the ecological impacts of polluted surface waters percolating underground (Di Lorenzo et al ., 2015, 2021; Manenti et al ., 2021), the long‐term consequences of climate change on specialised subterranean organisms adapted to thermally stable conditions (Mammola et al ., 2019c; Pallarés et al ., 2020a,b; Colado et al ., 2022), and some of the negative impacts that pathogens and alien species can cause to subterranean ecosystems (Howarth et al ., 2007; Wynne et al ., 2014; Howarth & Stone, 2020; Hoyt, Kilpatrick & Langwig, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To date, conservation of subterranean ecosystems has been dominated by problem‐based studies focused on identifying the main drivers associated with subterranean biodiversity decline (Mammola et al ., 2019a; Gerovasileiou & Bianchi, 2021). For example, we have elucidated the ecological impacts of polluted surface waters percolating underground (Di Lorenzo et al ., 2015, 2021; Manenti et al ., 2021), the long‐term consequences of climate change on specialised subterranean organisms adapted to thermally stable conditions (Mammola et al ., 2019c; Pallarés et al ., 2020a,b; Colado et al ., 2022), and some of the negative impacts that pathogens and alien species can cause to subterranean ecosystems (Howarth et al ., 2007; Wynne et al ., 2014; Howarth & Stone, 2020; Hoyt, Kilpatrick & Langwig, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, small variations in temperature would have severe consequences for the survival and fitness of tropical species (Deutsch et al, 2008;Ghalambor, 2006). However, other studies have shown that some temperate species may be equally vulnerable to climate change (Colado et al, 2022;Johansson et al, 2020;Mi et al, 2022). For example, temperate species with short activity periods may only experience narrow ranges in temperature (Johansson et al, 2020) and may be selected for low thermal tolerance in a similar way to tropical species (Colado et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the HSR in organisms from thermally stable subterranean habitats, including their associated inducible HSPs and at which temperatures this response might be activated, is scarce, with only a few studies devoted to invertebrate taxa 14 , 19 25 . However, invertebrates overwhelmingly contribute to the biodiversity of subterranean habitats compared to vertebrates 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%